Bushen Huoxue prescription inhibits ferroptosis of HUVEC cells by regulating FABP1-mediated lipid metabolism - Chen, Jingyi; Song, Xiaoying; Xie, Jiajie; Lou, Danfei (Frontiers in Pharmacology, 2025)
IntroductionAtherosclerosis (AS) is a chronic inflammatory disease with vascular homeostasis imbalance, whose main characteristics are plaque formation and lipid accumulation. In traditional Chinese medicine, AS is associated with kidney deficiency and blood stasis. Bushen Huoxue prescription (BSHXP), based on the principle of tonifying the kidney and promoting blood circulation, has been widely used in clinical practice. However, its effects on AS are still indeterminate. This study aims to explore the effects and related mechanisms of BSHXP on oxidized low-density lipoprotein (ox-LDL)-induced HUVEC cells.MethodsOx-LDL-induced HUVEC injury models were established by the ox-LDL incubation for 24 h, followed by BSHXP (12.5, 25, and 50 μg/mL) treatment. Cell viability was measured by MTT assay. Lipid metabolism was assessed by the Nile Red and Oil Red O staining. Inflammatory cytokines and ferroptosis markers were determined. Apoptosis was detected by Annexin V-FITC/PI staining.ResultsUHPLC-Q/Exactive identified 8 main metabolites. Network pharmacology predicted 12 core metabolites, 10 hub targets, and key pathways related to lipid metabolism and ferroptosis. BSHXP regulated lipid metabolism by reducing FABP1 and SREBP2 expression and decreasing lipid droplet accumulation (P < 0.05). BSHXP inhibited ferroptosis by lowering Fe2+, ROS, ACSL4, and 4-HNE levels while increasing GSH, GPX4, and SLC7A11 (P < 0.05). FABP1 knockdown had similar effects, while FABP1 overexpression and ferroptosis inducer Erastin reversed the effects of BSHXP (P < 0.05). BSHXP also reduced IL-1β, IL-6, MCP-1, VCAM-1, and apoptosis (P < 0.05).ConclusionBSHXP alleviates ox-LDL-induced HUVEC injury by inhibiting ferroptosis through FABP1-mediated lipid metabolism regulation.